An exploratory study on the perceptions of rabies and ill-health causations and health seeking behaviours of school children and local communities in southern Bhutan - Lungten, Lungten; Tenzin, Tenzin; Thys, Severine; Phimpraphai, Waraphon; Rinchen, Sangay; de Garine-Wichatitsky, Michel (BMC public health, 2023)
The perception of illness and health-seeking behaviours, including rabies differ from one culture to another. Depending on the cultural setting of the society in which people live, the definition of the causal factors of illness may range from natural biological causes to supernational causes which greatly influence subsequent health-seeking behaviour. To ensure best health practices and plan effective health interventions for the control of dog-mediated-human rabies, we explored how school children and adult communities perceive and respond to illnesses, including rabies in southern Bhutan. We collected quantitative data related to the causes of illness and health-seeking practices of school children using a questionnaire survey (QS). Qualitative data were collected through focus group discussions (FGDs) and in-depth interviews (IDIs) with older members of communities (≥ 18 years) that work closely with school children. Descriptive analysis was performed for the quantitative data and thematic analysis was performed for the qualitative data. The participants during the FDGsand IDIshave linked the illnesses to past actions, spirits, energy channels, planetary movement, sorcery, black magic, food, physical or environmental factors, individual habits and social factors. The survey of the school children reported microorganisms (75%), past actions (16.8%), spirits (9.6%) and black magic (9.1%) as causal factors for illnesses. Health seeking behaviours reported by the participants included visiting hospitals, performing spiritual or religious rituals and local treatments. Similarly, school children also mentioned that illnesses can be treated by visiting hospitals (98%), performing rituals (59.1%), and seeking traditional treatments practices (18.8%). Both school children and adult members of the communities that we interviewed were well aware on the causes of rabies and need for allopathic treatments rather than seeking spiritual or local treatments. There is a need for the consideration of the socio-cultural context in the planning and implementation of health-related policies, including the rabies prevention programs in Bhutan, by involving traditional healers and religious entities with "One Health" public health sectors.